Предмет: Математика,
автор: karinaaadelina
Составьте сумму выражений -m+n и -k-n и упростите ее
Ответы
Автор ответа:
0
(x+12) + (-16-x) = x +12 - 16 - x = -4
(4,8+n) - (-6,3+n)= 4.8 + n + 6.3 - n = 11.1.
(4,8+n) - (-6,3+n)= 4.8 + n + 6.3 - n = 11.1.
Автор ответа:
0
-m+n-k-n=-m-k
!!!!!!!!!!!!!!!!!!!!!!!!!!
!!!!!!!!!!!!!!!!!!!!!!!!!!
Похожие вопросы
Предмет: Математика,
автор: gorohovaliliia0
Предмет: Русский язык,
автор: ganievasafina67
Предмет: Английский язык,
автор: zanararysbaeva87
Предмет: Биология,
автор: katiusa88